Review: static and dynamic behavior of liquids inside carbon nanotubes - Mattia, Davide; Gogotsi, Yury (Microfluidics and nanofluidics, 2008)
This review deals with the static and dynamic behavior of liquids inside carbon nanotubes, a broad subject, which includes: the investigation of liquid entering inside the tubes, and the subsequent filling of them, the overall flow through tubes as well as the wetting of the nanotube walls. Although most of the numerical work has been done on small diameter nanotubes, due to computational limitations, a large wealth of experimental results have been obtained for larger diameter nanotubes, between 10 and 100 nm, or above. This review offers an overview of the major achievements in the field, with particular emphasis on the effect on liquid flow through them of the structure and chemistry of carbon nanotubes. The limit below which liquids confined in nanotubes will not obey classical fluid dynamics equations as well as the structure and state of liquids under confinement will also be reviewed. Finally, near-to commercialization and still-in-the-lab applications will be covered.